Análise dos distúrbios no transitório de partida de motores de indução trifásicos - PINHEIRO, Diego da Silva (2018)
In virtually all industrial processes are used single-phase and three-phase induction motors because of its good performance and low constructive and maintenance costs. The electric motors during starting, which has a duration of around 0.5 to 10 seconds, require high drive currents ranging from 6 to 10 times its rated current. In this transition the power electric system suffers some disturbances of which we can highlight falls in rms values of the supply voltage, harmonics and interharmônicos which consequently bring damages to the engine itself, the protection system, drive, and other devices and equipment that are interconnected yourself distribution bus [1]. Because of these inherent characteristics of asynchronous electric motors, adopt up for direct, indirect and electronic games systems to mainly solve the problem of overcurrent in the initiation of these machines, however when adopting these methods, on the other hand have been changes in parameters of influence directly in power quality as for examples the excitement of different fundamental frequencies. The main and most widespread types of matches, which will make the simulation and implementation in the laboratory are: Direct start, triangle wrench through rewarding key, frequency inverter. These drive systems are used mostly to induction motors MIT, but in reality these problems are also applied to single-phase ME induction motors as centrifugal pumps. Therefore, this work presents an analysis of disorders caused by different types of drives and a comparison of the efficiency of each based on criteria for quality of electricity. In developing this work were collected data analyzed by Fluke 435 Power Quality Methods of direct starting, star-delta and with frequency inverter presented THD indices above those permitted in the IEEE 1531-2003 standard, while the method of rewarding starting with autotransformer presented a THD index at baseline. The frequency inverter presented indexes above the permitted, reaching 154.1% THD, thus requiring mitigation methods, such as filters.